Targeting the renin-angiotensin system: potential beneficial effects of the angiotensin II receptor bloxkers in patients with nonalcholic steatohepatitis. - Sookoian, Silvia Cristina (2011)
Fil: Sookoian, Silvia Cristina. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Oficina de Coordinacion Administrativa Houssay. Instituto de Investigaciones Medicas; Argentina. Universidad de Buenos Aires. Facultad de Medicina. Instituto de Investigaciones Médicas; Argentina